2020
DOI: 10.5114/kitp.2020.99074
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in blunt chest trauma: a cross-sectional study

Abstract: Introduction: Trauma is the most common cause of presentation to hospital emergency services. After extremity and cranial injuries, blunt thoracic trauma is the third most common injury. Aim: In this study, we aimed to present and assess blunt chest trauma in adults aged below 65 and elderly (age ≥ 65). Material and methods: In this study, 130 patients (86 young (age 18-64) and 44 elderly (age ≥ 65)) who applied to the emergency department with blunt thoracic trauma between October 2017 and October 2019 were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Regarding thoracic cage fracture and rib fracture, they were present in 11 adult patients (33.3%), 2 of them were flail chest in comparison with only one child (7.1%) with rib fracture and absence of flail chest. This is in accordance with Kapicibasi (8) who stated that rib fracture and flail chest were significantly more frequent in the elderly group compared to the younger patients.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding thoracic cage fracture and rib fracture, they were present in 11 adult patients (33.3%), 2 of them were flail chest in comparison with only one child (7.1%) with rib fracture and absence of flail chest. This is in accordance with Kapicibasi (8) who stated that rib fracture and flail chest were significantly more frequent in the elderly group compared to the younger patients.…”
Section: Discussionsupporting
confidence: 92%
“…There were 50 studies of varying design and quality which investigated whether age was a risk factor for mortality in patients with blunt chest wall trauma (online supplemental file 3, table 1). Of these, 19 studies demonstrated a higher risk of mortality in patients aged 65 years or more when compared with patients aged less than 65 years 7 13–16 30–43. Other studies demonstrated that increased risk of mortality occurred in patients aged 50 years or more,17 55 years or more,44 45 60 years or more,46–50 70 years or more,51 80 years or more,52 and 90 years or more 53.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies demonstrated an increasing risk of mortality per additional year of age5 54–56 and others with an additional decade 2 14 57. In 14 studies age was not found to be a statistically significant risk factor for increased mortality,3 37 58–69 however it is worth noting that 4 of these studies used aged 45 years or more as the cut-off for increased risk 58 63 67 69…”
Section: Resultsmentioning
confidence: 99%
“…9 All the studies reported that most common type of chest injuries are blunt chest trauma. [6][7][8][9][10][11][12] In our study, young adults' males with a mean age of 32 years old were found to be more prone to RTA, this could be related to the legal system and regulations in Saudi Arabia, as previously prohibits women from driving. Furthermore, this could also due to most of the Saudi population belong to the younger age group and may be this group is predisposed to reckless driving behavior.…”
Section: Discussionmentioning
confidence: 89%